Planning in the USA. Policies, issues and processes. 2nd. edition. - Cullingworth, Barry; Caves, Roger W. (Routledge, 2003)
Der Band gibt eine Einführung in das Planungssystem der Vereinigten Staaten. In sechs Abschnitten werden die Themenfelder Planung und Verwaltung (mit der Stellung der Kommunen und der kommunalen Planung, Bürgerbeteiligung), Flächenutzungsplanung (Flächennutzungsplan, Bebauungsplan, Baulandentwicklung, Flächenbereitstellung), Stadtgestaltung (Stadtbildpflege, Ortssatzungen, Denkmalschutz), Stadtwachstum und Wachstumssteuerung (Außen- und Innenentwicklung), Stadtentwicklungsplanung (Verkehrsplanung, Wohnungspolitik, Wirtschaftspolitik), Umweltschutz (Luftreinhaltung, Wassergüte, Entsorgung) in ihren rechtlichen Grundlagen, ihrer politischen Ausgestaltung und in hostorischen und aktuellen Fallbespielen erläutert.

This extensively revised and updated second edition of Planning in the USA continues to provide a comprehensive introduction to the policies, theory and practice of planning. Outlining land use, urban planning and environmental protection policies, this fully illustrated book explains the nature of the planning process and the way in which policy issues are identified, defined and approached. The second edition incorporates new planning legislation and regulations at the state and federal layers of government, and examples of local ordinances in a variety of planning areas. New material includes: the role of citizen participation and how planners can obtain it; the use of Geographical Information Systems (GIS) in planning; a discussion of the 'Rural Renaissance' population movement; the need for infrastructure to be concurrent with development; the major 'Smart Growth' movement; zoning innovations; a discussion of multiple species conservation planning, habitat conservation planning and sustainability. The book gives a detailed account of urbanization in the United States and reveals the problematic nature and limitations of the planning process, the fallibility of experts and the difficulties facing policy makers in their search for solutions. Planning in the USA is an essential book for students, planners and all who are concerned with the nature of contemporary urban and environmental problems.
Keywords: Raumplanung; Stadtplanung; Stadtgestaltung; Bebauungsplanung; Freiraumplanung; Freifläche; Planungssystem; Planungsprozess; Planungsrecht; Denkmalschutz; Umweltschutz; Umweltplanung; Entsorgung; Partizipation; Fallstudie; Innenentwicklung; Nachhaltigkeit; Geoinformationssystem